The Little Green Data Book 2005 - World Bank (World Development Indicators, 2005)
In its 4rd annual edition, The Little Green Data Book 2005 is a pocket-sized ready reference on key environmental data for over 200 countries. Key indicators are organized under the headings of agriculture, forestry, biodiversity, energy, emission and pollution, and water and sanitation. Profiles of each country include 48 key development indicators like: Population, Urban Population, Rural Population Density; GNI, GDP, Gross National Savings; Forest Area, Annual Deforestation; Agricultural Land, Fertilizer Consumption, Irrigated Land, Food Production Index; Mammal and Bird Species Threatened; Electric Power Consumption, GDP per unit of energy use; CO2 Emissions per Capita, Passenger Cars; Freshwater resources per capita, Access to Sanitation; Energy Depletion, Education Expenditure, Under-5 Mortality Rate. Drawing on data from the World Bank's World Development Indicators 2005, The Little Green Data Book provides quick reference to the latest available environmental data for World Bank member countries as well as other economies with populations of over 30,000